Study of the motor mechanisms of the underwater phase of the start of a para-swimmer with unilateral lower limb deficiency - Vinokourov L.V.; Lebedeva A.L.; Baymuratov I.A.; Kaipov Ju.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify and describe the mechanism of underwater wave-like swimming in swimmers with unilateral lower limb deficiency. Methods and structure of the study. Video recording of the underwater phase of the start and analysis of video materials, stereoscopic analysis of movements with measurement of fluid flow velocity and vortex formation, assessment of the range of rotation of the leg joints, mathematical and statistical methods were used. Results and conclusions. It has been established that the mechanism of propulsion in the underwater phase after the start in swimmers with lower limb deficiencies differs from that in healthy swimmers in that they are unable to generate paired vortices and move by releasing a vortex created by only one leg. At the same time, a large vortex around the foot is created when striking downwards, and a small one when striking upwards. The range of hip rotation in swimmers with an amputated leg is smaller than in healthy swimmers.